The Legacy of the Soviet Agricultural Research System for the Republics of Central Asia and Caucacus - International Service for National Agricultural Research (International Service for National Agricultural Research, 1999)
Historically, Russia and then the Soviet Union, were largely agricultural countries, at least up to the 1950s. The majority of the population lived in the countryside and was involved in crop cultivation and animal husbandry. Agriculture progressed as the society progressed and, at a certain stage of its development, agricultural science became an integral part of its evolution. The beginning of agricultural science in Russia is probably associated with the establishment of the Russian Academy of Sciences by Peter the Great in 1724. A notable scientist of the time, Mikhail Lomonosov (1711-1765), was the first to establish a separate structure within the Academy with the responsibility for assistance to agriculture. The first scientist in Russia who conducted experiments and published a number of books on agriculture was Andrey Bolotov (1738-1833), military officer and a land owner (Nikonov, 1995). In 1765, Katherine II issued a decree establishing the Imperial Liberal Economic Society with the major objective to assist in the development of agriculture in Russia. The Society conducted experiments and published books and journals on a number of agricultural subjects such as soil science, bee-keeping, veterinary, agronomy, animal husbandry and others. The activity of the Society was stopped in 1915 because some of its members were suspected of socialist activities. Agricultural science in the 19th century was mainly concentrated in universities in Moscow, St. Petersburg and other large cities. In the second part of the 19th century, specialized agricultural universities and colleges were established. The first two were Gorygoretsk Agricultural College established in 1848 (now Belorussian Agricultural Academy) and Petrovskaya Agricultural Academy established in 1865 (now Timiryazev Moscow Agricultural Academy). By the beginning of the 20th century, very detailed knowledge was accumulated on farming systems, crop rotations, mineral nutrition, soil fertility, cropping in dry environments and many other subjects. According to the 1897 census data, 85% of the population in Russia lived in the countryside and 74% depended entirely on production from their farms (Nikonov, 1995, page 74). At the same time, the country exported 33% of its wheat and 41% of its barley production (Nikonov, 1995, page 72). The end of the 19th century and the beginning of the 20th (period of 1890-1915) witnessed a large increase in the number of agricultural research and educational institutions. This was influenced by several factors such as a favorable economic situation before World War I, a rapid increase in agricultural production as a result of the liberal reforms conducted by the government in 1906-1911, and the high priority given by the government to agricultural production. This change was reflected in the increase of the total budget of the Department (Ministry) of Agriculture from 2.4 million rubles in 1895 to 29.4 million rubles in 1913. Also, in 1910 there were 239 agricultural educational institutions (courses of all levels, schools, colleges, universities) and by 1915 the number was 341. At the same time, the government share of funding for these institutions increased from 42% to 60%.